ENTREPRENEURSHIP IN MYANMAR: PROPOSING SOLUTIONS TO DIGITAL CHALLENGES THROUGH ECOSYSTEM AND STRATEGIC FRAMEWORKS - Ei Khin Khin (Universitas Budi Luhur, 2025)
Abstract: This research investigates the challenges faced by youth entrepreneurs in Myanmar, with a focus on those navigating the digital entrepreneurship space. It examines the impact of Myanmar's socio-political environment, particularly following the 2021 military coup, on business operations, access to financial resources, and overall entrepreneurial development. The study highlights the barriers young entrepreneurs encounter, such as economic instability, infrastructure deficiencies, and limited market access. Through a qualitative research design, data was collected from four digital entrepreneurs via semi-structured surveys, and analyzed using an entrepreneurship ecosystem framework. Key challenges identified include financial constraints, inadequate infrastructure, and a restrictive policy environment. Despite these obstacles, entrepreneurs displayed resilience through innovative strategies, emphasizing the importance of adaptability, networking, and continual learning. The research also proposes strategic solutions to address these challenges, including fostering public-private partnerships for infrastructure development, improving policy frameworks to protect and encourage digital entrepreneurship, and providing mental health and business skills support for young entrepreneurs. The findings provide practical guidance for policymakers, business incubators, and other stakeholders to create a more supportive ecosystem that empowers Myanmar’s youth to thrive in the digital economy. Ultimately, the study underscores the need for systemic reforms and targeted interventions to unlock the full potential of Myanmar’s entrepreneurial landscape. Abstrak: Penelitian ini menyelidiki tantangan yang dihadapi oleh pengusaha muda di Myanmar, dengan fokus pada mereka yang menjelajahi ruang kewirausahaan digital. Artikel ini meneliti dampak lingkungan sosial-politik Myanmar, terutama setelah kudeta militer 2021, terhadap operasi bisnis, akses ke sumber daya keuangan, dan perkembangan kewirausahaan secara keseluruhan. Selanjutnya, artikel ini menyoroti hambatan yang dihadapi oleh para pengusaha muda, seperti ketidakstabilan ekonomi, kekurangan infrastruktur, dan akses pasar yang terbatas. Melalui desain penelitian kualitatif, data dikumpulkan dari empat pengusaha digital melalui survei semi-terstruktur, dan dianalisis menggunakan kerangka ekosistem kewirausahaan. Tantangan utama yang teridentifikasi meliputi keterbatasan finansial, infrastruktur yang tidak memadai, dan lingkungan kebijakan yang membatasi. Meskipun menghadapi berbagai rintangan ini, para pengusaha menunjukkan ketahanan melalui strategi inovatif, menekankan pentingnya adaptabilitas, jaringan, dan pembelajaran berkelanjutan. Penelitian ini juga mengusulkan solusi strategis untuk mengatasi tantangan-tantangan ini, termasuk mendorong kemitraan publik-swasta untuk pengembangan infrastruktur, memperbaiki kerangka kebijakan untuk melindungi dan mendorong kewirausahaan digital, serta menyediakan dukungan kesehatan mental dan keterampilan bisnis bagi para wirausahawan muda. Temuan tersebut memberikan panduan praktis bagi pembuat kebijakan, inkubator bisnis, dan pemangku kepentingan lainnya untuk menciptakan ekosistem yang lebih mendukung yang memberdayakan pemuda Myanmar untuk berkembang dalam ekonomi digital. Pada akhirnya, studi ini menekankan perlunya reformasi sistemik dan intervensi yang terarah untuk membuka potensi penuh lanskap kewirausahaan Myanmar.